(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A survey was conducted during 2011-2012 in Khartoum State. The surveyfocused on the identification of insects associated with stored onion. Insects encounteredwere, the fig moth (Ephestia cautella), the dried fruit beetle (Carpophilus hemipterus),the sap beetle (Carpophilus obsolitus), the humpbacked fly (Megaselia scalaris), the antbeetle (Anthicus floralis), the hairy fungus beetle (Typhaea stercorea), the confused flourbeetle (Triboleum confusum), the scavenger fly (Chrysomyza demandata), the dungbeetle (Aphodius lividus), the minute pirate bug (Orius leavigatus), and the rove beetles(Aleochara bipustulata, four Quidius spp. and Lithocharis sp.).